Preparation method of aluminum nitride light-emitting diode

By growing AlN layers on beveled sapphire substrates and using a superlattice transition layer, the method addresses poor performance and production costs of AlN LEDs, achieving high-quality, mass-producible, and efficient AlN LEDs with reduced dislocation density and improved thermal stability.

CN119153595AInactive Publication Date: 2024-12-17FUJIAN HUAQING ELECTRONICS MATERIAL TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411286047.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing aluminum nitride light-emitting diodes (LEDs) suffer from poor performance, high production costs, and are not suitable for mass production due to issues such as high dislocation density, defects, and impurities in the AlN layer, which affect luminous efficiency and stability.

Method used

A method involving the growth of high-quality AlN layers on beveled sapphire substrates using metal organic chemical vapor deposition (MOCVD), with specific temperature, pressure, and growth rate adjustments, followed by the introduction of a superlattice transition layer to reduce dislocation density and enhance lattice matching, and packaging with a composite filler to improve thermal conductivity and adhesion.

Benefits of technology

The method results in high-performance, crack-free AlN LEDs with reduced dislocation density, enabling mass production and improved luminous efficiency, thermal stability, and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153595A_ABST
    Figure CN119153595A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoelectron manufacturing, provides a preparation method of an aluminum nitride light-emitting diode, and solves the problems that a light-emitting diode prepared in the prior art is relatively poor in performance, high in production cost and not suitable for mass production. Comprising the following steps: 1) sequentially growing a first AlN layer, a second AlN layer, a third AlN layer, a superlattice transition layer, an n-AlGaN layer, a multi-quantum well light-emitting layer and a P-AlGaN layer on the surface of a sapphire substrate subjected to beveling treatment; 2) preparing an electrode; and 3) packaging to obtain the aluminum nitride light-emitting diode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optoelectronic manufacturing, and in particular to a method for preparing an aluminum nitride light emitting diode. Background Art

[0002] Aluminum nitride (AlN), as an advanced ceramic material with excellent thermal conductivity, high hardness and good chemical stability, has long shown great potential in the fields of microelectronic packaging, thermal management and deep ultraviolet optoelectronic devices.

[0003] The emergence of aluminum nitride light-emitting diodes marks an important leap in the field of optoelectronic technology. Traditional LED materials such as silicon (Si) and gallium nitride (GaN) have excellent luminous efficiency within a specific wavelength range, but when pursuing light sources with shorter wavelengths (such as the deep ultraviolet region), these materials face challenges such as reduced efficiency and increased costs. Aluminum nitride, with its unique crystal structure and electronic properties, can theoretically achieve efficient and stable deep ultraviolet light emission, providing unprecedented solutions for sterilization, water purification, medical testing, non-contact sensing and other fields.

[0004] Chinese patent application No. 202310609857.2 discloses a method for preparing a light-emitting diode and a diode, the preparation method comprising: providing a substrate; depositing a buffer layer, an undoped GaN layer, an n-type GaN layer, a multi-quantum well layer, an electron blocking layer, a P-type defect blocking layer and a P-type GaN layer on the substrate in sequence; wherein the P-type defect blocking layer comprises a Mg-doped AlN layer, a first GaN healing layer, a second GaN healing layer, and a Mg-doped AlGaN layer deposited in sequence on the electron blocking layer; after the first GaN healing layer is deposited, the surface of the first GaN healing layer is pretreated. The invention reduces the leakage channel, reduces the current concentration effect, and improves the luminous efficiency of the light-emitting diode by inserting a layer of P-type defect blocking layer between the electron blocking layer and the P-type GaN layer. However, the light-emitting diode does not have a second AlN layer containing voids, and the deposited buffer layer formed does not have the characteristics of high quality and low dislocation density, so the performance of the prepared light-emitting diode is relatively poor.

[0005] Chinese patent application No. 202410748380.0 discloses a method for preparing a single crystal growth of a light-emitting diode, which comprises: single crystal growth of an AlN layer, an AlGaN transition layer, an undoped GaN layer, an n-type GaN layer, a single crystal growth quantum well harmonic layer, a first quantum well layer, a second quantum well layer, a third quantum well layer, a fourth quantum well layer, a first P-type GaN layer, an AlGaN electron blocking layer, a second P-type GaN layer, and a third P-type GaN layer on a substrate, forming a light-emitting diode with in-situ voids inside and emitting four different peak wavelengths of blue light, generating a free space surface inside the material through in-situ voids, blocking dislocations from extending upward, and achieving an improvement in the crystal quality of the single crystal growth material, thereby improving the luminous efficiency and antistatic ability of the light-emitting diode. However, the substrate of the light-emitting diode single crystal has not been beveled, and there will still be defects and impurities in the AlN layer grown on this substrate, and the obtained AlN layer has a relatively high dislocation density, which affects the performance of the light-emitting diode. Summary of the invention

[0006] Therefore, in view of the above problems, the present invention provides a method for preparing an aluminum nitride light emitting diode, which solves the problem that the light emitting diode prepared by the prior art has relatively poor performance, high production cost and is not suitable for mass production.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing an aluminum nitride light emitting diode comprises the following steps:

[0009] S1. Growth of the first AlN layer: adjusting the temperature to 1000-1050° C., V / III1 to 1000, adjusting the pressure to 55-60 mbar, and the growth rate to 0.55-0.60 μm / h, and growing the first AlN layer on the surface of the beveled sapphire substrate;

[0010] S2, growing a second AlN layer: adjusting the temperature to 900-950° C., V / III1 to 5000, adjusting the pressure to 100-105 mbar, and the growth rate to 0.30-0.35 μm / h, and continuing to grow the second AlN layer on the surface of the first AlN layer;

[0011] S3, growing a third AlN layer: adjusting the temperature to 1100-1150° C., V / III1 to 50, adjusting the pressure to 50-55 mbar, and the growth rate to 2.0-2.4 μm / h, and continuing to grow the third AlN layer on the surface of the second AlN layer;

[0012] S4, growing a superlattice transition layer: adjusting the temperature to 1000-1050° C., V / III1 to 850, adjusting the pressure to 100-105 mbar, and the growth rate to 1-1.05 μm / h, and continuing to grow a superlattice transition layer on the surface of the third AlN layer;

[0013] S5, growing an n-AlGaN layer: adjusting the temperature to 1000-1050° C., V / III2 to 850, adjusting the pressure to 100-105 mbar, and the growth rate to 1-1.05 μm / h, and continuing to grow the n-AlGaN layer on the surface of the superlattice transition layer;

[0014] S6, growing multi-quantum well light-emitting layer: at a silicon doping concentration of 1.0-1.2×10 19 / cm -3 Under the condition of, adjusting the temperature to 750-780° C., growing a multi-quantum well light-emitting layer on the surface of the n-AlGaN layer;

[0015] S7, growing a P-AlGaN layer: keeping the growth environment unchanged, continuing to grow the P-AlGaN layer, the P-AlGaN layer including a p-AlGaN layer located at a lower layer and a p-GaN layer located at an upper layer, after the growth is completed, obtaining an epitaxial wafer, and keeping the epitaxial wafer at 750° C. in a N2 protective atmosphere for 10 minutes to obtain a light-emitting diode chip;

[0016] S8, preparing electrodes: coating photoresist on the surface of the light-emitting diode chip, drying, exposing, developing, and drying again, then using electroplating to deposit electrode metal, and then removing excess parts by etching;

[0017] S9, packaging: applying solder paste to the two metal electrodes of the bracket, and then applying a composite filler to the spacer between the two metal electrodes of the bracket, solidifying the light-emitting diode chip processed in step S8, and after reflow soldering, filling with silica gel and curing, to obtain the aluminum nitride light-emitting diode;

[0018] Among them, the V / III1 is: the ratio of the molar flow rate of the group V source to the molar flow rate of the group III1 source; the group V source is NH3, and the group III1 source is trimethylaluminum; V / III2 is: the ratio of the molar flow rate of the group V source to the molar flow rate of the group III2 source, and the group III2 source is trimethylgallium or triethylgallium.

[0019] Furthermore, the beveling process is as follows: the beveling direction is from the c-plane to the a-plane or from the c-plane to the m-plane; the beveling angle is 0°, 4°, 6° from the c-plane to the a-plane or 4°, 6° from the c-plane to the m-plane.

[0020] Furthermore, the composite filler comprises the following raw materials in parts by weight: 0.5-1 parts of AlN powder, 1-2 parts of Al2O3 powder, and 2-4 parts of thermal conductive glue, wherein the thermal conductive glue is thermal conductive glue DC340; the solder paste is Sn 96.5 Ag3Cu 0.5 ; The bracket is epoxy resin.

[0021] Furthermore, the steps S1 to S7 are all performed in a metal organic chemical vapor deposition device.

[0022] Furthermore, the thickness of the first AlN layer is 300-320 nm, the thickness of the second AlN layer is 100-250 nm, the thickness of the third AlN layer is 350-650 nm, the thickness of the superlattice transition layer is 500-520 nm, and the thickness of the n-AlGaN layer is 2 μm.

[0023] Furthermore, the multi-quantum well light-emitting layer includes 5-12 periods, each period includes a well layer located at the lower layer and a barrier layer located at the upper layer, the thickness of the well layer is 2-3 nm, and the thickness of the barrier layer is 10 nm.

[0024] Furthermore, the die bonding is to place the LED chip on a bracket dotted with a composite filler; the reflow soldering is to melt the solder paste and fix the LED chip; the curing is carried out in a drying oven at a temperature of 120-150°C for 2-4 hours.

[0025] By adopting the above technical solution, the beneficial effects of the present invention are:

[0026] 1. Growing high-quality, low-dislocation-density AlN layers is the premise and key to achieving high-performance light-emitting diodes. Beveling the sapphire substrate can reduce the number and types of defects by changing the stress distribution and defect generation mechanism during the growth of the AlN layer, and can obtain a high-quality AlN layer. Beveling can guide dislocations to slip or annihilate in a specific direction, thereby reducing the dislocation density of the AlN layer; beveling can also affect the diffusion and capture behavior of impurities, helping to reduce the adverse effects of impurities on crystal performance;

[0027] 2. The AlN layer is grown on a sapphire substrate with excellent thermal and electrical conductivity. The process is mature and low-cost, and can be mass-produced.

[0028] 3. Using metal organic chemical vapor deposition technology, the first AlN layer is grown on the beveled surface. The surface of this layer is flat and has no holes. At this time, the dislocation density is high, which provides a basis for the subsequent growth of the second AlN layer. Then adjust the temperature to 900-950℃ and V / III1 to 5000. The surface migration ability of Al atoms is low under the growth conditions of lower temperature and higher V / III1. The mass transport of the surface is suppressed during the epitaxial growth process, forming an in-situ void layer, i.e., the second AlN layer. The surface of this layer is rough and has high-density holes. Then the second AlN layer After the holes on the surface are formed and reach a certain diameter and density, the temperature is adjusted to 1100-1150°C and V / III1 is 50, that is, the third AlN layer is grown under the growth conditions of high temperature and low V / III1. The surface flatness of the layer is gradually improved, and the holes are buried inside the material, so that a second AlN layer containing holes is formed between the first and third AlN layers. The holes are used to provide space for the strain of AlN under the action of tensile stress, thereby relaxing part of the tensile stress and inhibiting the generation of cracks in the epitaxial layer. Finally, a crack-free epitaxial wafer with high lattice relaxation is grown on the sapphire substrate;

[0029] 4. A superlattice transition layer is introduced between the third AlN layer and the n-AlGaN layer to achieve a gradual change in the lattice constant and compressive stress from the third AlN layer to the n-AlGaN layer, thereby suppressing the generation of mismatch dislocations and surface three-dimensional growth caused by lattice and stress mutations, greatly improving the surface flatness of the sample, and also suppressing the in-plane phase separation phenomenon, avoiding lattice mismatch between the third AlN and n-AlGaN layers, and reducing dislocation density;

[0030] 5. The light-emitting diode chip is solidified on the epoxy resin bracket through solder paste, and a composite filler is added to the spacer between the two metal electrodes of the bracket. This can reduce the impact of thermal shock on the p-GaN layer of the light-emitting diode, reduce the thermal resistance of the bonding layer, enhance the heat dissipation of the packaged chip, improve the adhesion of the light-emitting diode chip, reduce the fluidity of the solder paste during the reflow process, and avoid the displacement of the light-emitting diode chip. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a schematic diagram of the c-Plane crystal plane of the crystal structure of the sapphire substrate in Example 1 of the present invention;

[0032] Figure 2 is a schematic diagram of the crystal structure m-Plane of the sapphire substrate in Example 1 of the present invention;

[0033] Figure 3 is a schematic diagram of the a-Plane crystal surface of the crystal structure of the sapphire substrate in Example 1 of the present invention;

[0034] Figure 4is a schematic diagram of the r-Plane crystal plane of the crystal structure of the sapphire substrate in Example 1 of the present invention;

[0035] Figure 5 It is a schematic diagram of the n-Plane crystal plane of the crystal structure of the sapphire substrate in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] Example 1

[0037] A method for preparing an aluminum nitride light emitting diode comprises the following steps:

[0038] (1) Growth of the first AlN layer

[0039] (1-1) Bevel cutting of sapphire substrate

[0040] The bevel direction is from the c-plane to the a-plane; the bevel angle is 4° from the c-plane to the a-plane;

[0041] like Figures 1 to 5 As shown, the sapphire substrate is a single crystal α-Al2O3, which is composed of three oxygen atoms and two aluminum atoms combined in the form of covalent bonds, and its crystal structure is a hexagonal lattice structure. In the case of this molecular structure, the sapphire substrate has molecular layers in different directions, which will reflect X-rays, thereby generating crystal directions and forming five different crystal planes, namely c-Plane, m-Plane, a-Plane, r-Plane and n-Plane; a1, a2, and a3 are three a-axes, and the three a-axes are distributed at an angle of 120° on the same horizontal plane, and the c-Axis is perpendicular to the horizontal plane; the a-Plane and c-Plane are planes perpendicular to the a-axis and the c-axis respectively;

[0042] (1-2) growing a first AlN layer: adjusting the temperature to 1000° C., V / III1 to 1000, adjusting the pressure to 55 mbar, and the growth rate to 0.55 μm / h, and growing a first AlN layer with a thickness of 300 nm on the surface of the beveled sapphire substrate;

[0043] (2) growing a second AlN layer: adjusting the temperature to 900° C., V / III1 to 5000, adjusting the pressure to 100 mbar, and the growth rate to 0.30 μm / h, and continuing to grow a second AlN layer with a thickness of 100 nm on the surface of the first AlN layer;

[0044] (3) growing a third AlN layer: adjusting the temperature to 1100° C., V / III1 to 50, adjusting the pressure to 50 mbar, and the growth rate to 2.0 μm / h, and continuing to grow a third AlN layer with a thickness of 350 nm on the surface of the second AlN layer;

[0045] (4) growing a superlattice transition layer: adjusting the temperature to 1000° C., V / III1 to 850, adjusting the pressure to 100 mbar, and the growth rate to 1 μm / h, and continuing to grow a superlattice transition layer with a thickness of 500 nm on the surface of the third AlN layer;

[0046] (5) growing an n-AlGaN layer: adjusting the temperature to 1000° C., V / III2 to 850, adjusting the pressure to 100 mbar, and the growth rate to 1 μm / h, and continuing to grow an n-AlGaN layer with a thickness of 2 μm on the surface of the superlattice transition layer;

[0047] (6) Growth of multi-quantum well light-emitting layer: When the silicon doping concentration is 1.0×10 19 / cm -3 Under the condition of , adjusting the temperature to 750° C., growing a multi-quantum well light-emitting layer on the surface of the n-AlGaN layer, the multi-quantum well light-emitting layer comprising 5 periods, each period comprising a well layer located at a lower layer and a barrier layer located at an upper layer, the well layer having a thickness of 2 nm, and the barrier layer having a thickness of 10 nm;

[0048] (7) Growing a P-AlGaN layer: Keeping the growth environment unchanged, the P-AlGaN layer continues to grow, the P-AlGaN layer includes a p-AlGaN layer located at the bottom layer and a p-GaN layer located at the top layer. After the growth is completed, an epitaxial wafer is obtained, and the epitaxial wafer is kept at 750° C. in a N2 protective atmosphere for 10 minutes to obtain a light-emitting diode chip;

[0049] (8) Preparing electrodes: coating a photoresist on the surface of the light-emitting diode chip, drying, exposing, developing, and drying again, then using an electroplating process to deposit electrode metal, and then removing excess parts through corrosion treatment;

[0050] (9) Packaging

[0051] (9-1) Preparation of composite filler

[0052] The composite filler comprises the following raw materials in parts by weight: 0.5 parts of AlN powder, 1 part of Al2O3 powder, and 2 parts of thermal conductive glue, wherein the thermal conductive glue is thermal conductive glue DC340, and the raw materials are uniformly mixed according to parts by weight to obtain the composite filler;

[0053] (9-2) Packaging

[0054] Sn 96.5 Ag3Cu 0.5, then add a composite filler to the spacer between the two metal electrodes of the bracket, solidify the light-emitting diode chip treated in step (8), place the light-emitting diode chip on the bracket with the composite filler, reflow soldering to melt the solder paste, fix the light-emitting diode chip, fill with silica gel and solidify in a drying oven at a temperature of 120° C. for 2 hours to obtain the aluminum nitride light-emitting diode;

[0055] Wherein, V / III1 is the ratio of the molar flow rate of the group V source to the molar flow rate of the group III1 source; the group V source is NH3, and the group III1 source is trimethylaluminum; V / III2 is the ratio of the molar flow rate of the group V source to the molar flow rate of the group III2 source, and the group III2 source is trimethylgallium; steps (1) to (7) are all carried out in a metal organic chemical vapor deposition device.

[0056] Example 2

[0057] A method for preparing an aluminum nitride light emitting diode comprises the following steps:

[0058] (1) Growth of the first AlN layer

[0059] (1-1) Bevel cutting of sapphire substrate

[0060] The bevel direction is from the c-plane to the a-plane; the bevel angle is 6° from the c-plane to the a-plane;

[0061] (1-2) growing a first AlN layer: adjusting the temperature to 1020° C., V / III1 to 1000, adjusting the pressure to 58 mbar, and the growth rate to 0.58 μm / h, and growing a first AlN layer with a thickness of 310 nm on the surface of the beveled sapphire substrate;

[0062] (2) growing a second AlN layer: adjusting the temperature to 930° C., V / III1 to 5000, adjusting the pressure to 102 mbar, and the growth rate to 0.32 μm / h, and continuing to grow a second AlN layer with a thickness of 200 nm on the surface of the first AlN layer;

[0063] (3) growing a third AlN layer: adjusting the temperature to 1120° C., V / III1 to 50, adjusting the pressure to 52 mbar, and the growth rate to 2.2 μm / h, and continuing to grow a third AlN layer with a thickness of 500 nm on the surface of the second AlN layer;

[0064] (4) growing a superlattice transition layer: adjusting the temperature to 1020° C., V / III1 to 850, adjusting the pressure to 102 mbar, and the growth rate to 1 μm / h, and continuing to grow a superlattice transition layer with a thickness of 510 nm on the surface of the third AlN layer;

[0065] (5) growing an n-AlGaN layer: adjusting the temperature to 1020° C., V / III2 to 850, adjusting the pressure to 102 mbar, and the growth rate to 1 μm / h, and continuing to grow an n-AlGaN layer with a thickness of 2 μm on the surface of the superlattice transition layer;

[0066] (6) Growth of multi-quantum well light-emitting layer: When the silicon doping concentration is 1.1×10 19 / cm -3 Under the condition of , adjusting the temperature to 760° C., growing a multi-quantum well light-emitting layer on the surface of the n-AlGaN layer, the multi-quantum well light-emitting layer comprising 10 periods, each period comprising a well layer located at a lower layer and a barrier layer located at an upper layer, the well layer having a thickness of 3 nm, and the barrier layer having a thickness of 10 nm;

[0067] (7) Growing a P-AlGaN layer: Keeping the growth environment unchanged, the P-AlGaN layer continues to grow, the P-AlGaN layer includes a p-AlGaN layer located at the bottom layer and a p-GaN layer located at the top layer. After the growth is completed, an epitaxial wafer is obtained, and the epitaxial wafer is kept at 750° C. in a N2 protective atmosphere for 10 minutes to obtain a light-emitting diode chip;

[0068] (8) Preparing electrodes: coating a photoresist on the surface of the light-emitting diode chip, drying, exposing, developing, and drying again, then using an electroplating process to deposit electrode metal, and then removing excess parts through corrosion treatment;

[0069] (9) Packaging

[0070] (9-1) Preparation of composite filler

[0071] The composite filler comprises the following raw materials in parts by weight: 0.8 parts of AlN powder, 1.5 parts of Al2O3 powder, and 3 parts of thermal conductive glue, wherein the thermal conductive glue is thermal conductive glue DC340, and the raw materials are uniformly mixed according to parts by weight to obtain a composite filler;

[0072] (9-2) Packaging

[0073] Sn 96.5 Ag3Cu 0.5 , then add a composite filler to the spacer between the two metal electrodes of the bracket, solidify the light-emitting diode chip treated in step (8), place the light-emitting diode chip on the bracket on which the composite filler has been added, reflow soldering to melt the solder paste, fix the light-emitting diode chip, fill with silica gel and solidify in a drying oven at a temperature of 140° C. for 3 hours to obtain the aluminum nitride light-emitting diode;

[0074] Wherein, V / III1 is the ratio of the molar flow rate of the group V source to the molar flow rate of the group III1 source; the group V source is NH3, and the group III1 source is trimethylaluminum; V / III2 is the ratio of the molar flow rate of the group V source to the molar flow rate of the group III2 source, and the group III2 source is triethylgallium; steps (1) to (7) are all carried out in a metal organic chemical vapor deposition device.

[0075] Example 3

[0076] A method for preparing an aluminum nitride light emitting diode comprises the following steps:

[0077] (1) Growth of the first AlN layer

[0078] (1-1) Bevel cutting of sapphire substrate

[0079] The bevel direction is from the c-plane to the m-plane; the bevel angle is 4° from the c-plane to the m-plane;

[0080] (1-2) growing a first AlN layer: adjusting the temperature to 1050° C., V / III1 to 1000, adjusting the pressure to 60 mbar, and the growth rate to 0.60 μm / h, and growing a first AlN layer with a thickness of 320 nm on the surface of the beveled sapphire substrate;

[0081] (2) growing a second AlN layer: adjusting the temperature to 950° C., V / III1 to 5000, adjusting the pressure to 105 mbar, and the growth rate to 0.35 μm / h, and continuing to grow a second AlN layer with a thickness of 250 nm on the surface of the first AlN layer;

[0082] (3) growing a third AlN layer: adjusting the temperature to 1150° C., V / III1 to 50, adjusting the pressure to 55 mbar, and the growth rate to 2.4 μm / h, and continuing to grow a third AlN layer with a thickness of 650 nm on the surface of the second AlN layer;

[0083] (4) growing a superlattice transition layer: adjusting the temperature to 1050° C., V / III1 to 850, adjusting the pressure to 105 mbar, and the growth rate to 1.05 μm / h, and continuing to grow a superlattice transition layer with a thickness of 520 nm on the surface of the third AlN layer;

[0084] (5) growing an n-AlGaN layer: adjusting the temperature to 1050° C., V / III2 to 850, adjusting the pressure to 105 mbar, and the growth rate to 1.05 μm / h, and continuing to grow an n-AlGaN layer with a thickness of 2 μm on the surface of the superlattice transition layer;

[0085] (6) Growth of multi-quantum well light-emitting layer: When the silicon doping concentration is 1.2×10 19 / cm -3 Under the condition of , adjusting the temperature to 780° C., growing a multi-quantum well light-emitting layer on the surface of the n-AlGaN layer, the multi-quantum well light-emitting layer comprising 12 periods, each period comprising a well layer located at a lower layer and a barrier layer located at an upper layer, the well layer having a thickness of 2 nm, and the barrier layer having a thickness of 10 nm;

[0086] (7) Growing a P-AlGaN layer: Keeping the growth environment unchanged, the P-AlGaN layer continues to grow, the P-AlGaN layer includes a p-AlGaN layer located at the bottom layer and a p-GaN layer located at the top layer. After the growth is completed, an epitaxial wafer is obtained, and the epitaxial wafer is kept at 750° C. in a N2 protective atmosphere for 10 minutes to obtain a light-emitting diode chip;

[0087] (8) Preparing electrodes: coating a photoresist on the surface of the light-emitting diode chip, drying, exposing, developing, and drying again, then using an electroplating process to deposit electrode metal, and then removing excess parts through corrosion treatment;

[0088] (9) Packaging

[0089] (9-1) Preparation of composite filler

[0090] The composite filler comprises the following raw materials in parts by weight: 1 part of AlN powder, 2 parts of Al2O3 powder, and 4 parts of thermal conductive glue, wherein the thermal conductive glue is thermal conductive glue DC340, and the raw materials are uniformly mixed according to parts by weight to obtain the composite filler;

[0091] (9-2) Packaging

[0092] Sn 96.5 Ag3Cu 0.5 , then add a composite filler to the spacer between the two metal electrodes of the bracket, solidify the light-emitting diode chip treated in step (8), place the light-emitting diode chip on the bracket with the composite filler, reflow solder to melt the solder paste, fix the light-emitting diode chip, fill with silica gel and solidify in a drying oven at a temperature of 150° C. for 4 hours to obtain the aluminum nitride light-emitting diode;

[0093] Wherein, V / III1 is the ratio of the molar flow rate of the group V source to the molar flow rate of the group III1 source; the group V source is NH3, and the group III1 source is trimethylaluminum; V / III2 is the ratio of the molar flow rate of the group V source to the molar flow rate of the group III2 source, and the group III2 source is trimethylgallium; steps (1) to (7) are all carried out in a metal organic chemical vapor deposition device.

[0094] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.

Claims

1. A method for preparing an aluminum nitride light emitting diode, characterized in that: The following steps are involved: S1. Growth of the first AlN layer: adjusting the temperature to 1000-1050° C., V / III1 to 1000, adjusting the pressure to 55-60 mbar, and the growth rate to 0.55-0.60 μm / h, and growing the first AlN layer on the surface of the beveled sapphire substrate; S2, growing a second AlN layer: adjusting the temperature to 900-950° C., V / III1 to 5000, adjusting the pressure to 100-105 mbar, and the growth rate to 0.30-0.35 μm / h, and continuing to grow the second AlN layer on the surface of the first AlN layer; S3, growing a third AlN layer: adjusting the temperature to 1100-1150° C., V / III1 to 50, adjusting the pressure to 50-55 mbar, and the growth rate to 2.0-2.4 μm / h, and continuing to grow the third AlN layer on the surface of the second AlN layer; S4, growing a superlattice transition layer: adjusting the temperature to 1000-1050° C., V / III1 to 850, adjusting the pressure to 100-105 mbar, and the growth rate to 1-1.05 μm / h, and continuing to grow a superlattice transition layer on the surface of the third AlN layer; S5, growing an n-AlGaN layer: adjusting the temperature to 1000-1050° C., V / III2 to 850, adjusting the pressure to 100-105 mbar, and the growth rate to 1-1.05 μm / h, and continuing to grow the n-AlGaN layer on the surface of the superlattice transition layer; S6, growing multi-quantum well light-emitting layer: at a silicon doping concentration of 1.0-1.2×10 19 / cm -3 Under the condition of, adjusting the temperature to 750-780° C., growing a multi-quantum well light-emitting layer on the surface of the n-AlGaN layer; S7, growing a P-AlGaN layer: keeping the growth environment unchanged, continuing to grow the P-AlGaN layer, the P-AlGaN layer including a p-AlGaN layer located at a lower layer and a p-GaN layer located at an upper layer, after the growth is completed, obtaining an epitaxial wafer, and keeping the epitaxial wafer at 750° C. in a N2 protective atmosphere for 10 minutes to obtain a light-emitting diode chip; S8, preparing electrodes: coating photoresist on the surface of the light-emitting diode chip, drying, exposing, developing, and drying again, then using electroplating to deposit electrode metal, and then removing excess parts by etching; S9, packaging: applying solder paste to the two metal electrodes of the bracket, and then applying a composite filler to the spacer between the two metal electrodes of the bracket, solidifying the light-emitting diode chip processed in step S8, and after reflow soldering, filling with silica gel and curing, to obtain the aluminum nitride light-emitting diode; Among them, the V / III1 is: the ratio of the molar flow rate of the group V source to the molar flow rate of the group III1 source; the group V source is NH3, and the group III1 source is trimethylaluminum; V / III2 is: the ratio of the molar flow rate of the group V source to the molar flow rate of the group III2 source, and the group III2 source is trimethylgallium or triethylgallium.

2. The method for preparing an aluminum nitride light emitting diode according to claim 1, characterized in that: The beveling process is as follows: the beveling direction is from the c-plane to the a-plane or from the c-plane to the m-plane; the beveling angle is 0°, 4°, 6° from the c-plane to the a-plane or 4°, 6° from the c-plane to the m-plane.

3. The method for preparing an aluminum nitride light emitting diode according to claim 1, characterized in that: The composite filler comprises the following raw materials in parts by weight: 0.5-1 parts of AlN powder, 1-2 parts of Al2O3 powder, and 2-4 parts of thermal conductive glue, wherein the thermal conductive glue is thermal conductive glue DC340; the solder paste is Sn 96.5 Ag3Cu 0.5 ; The bracket is epoxy resin.

4. The method for preparing an aluminum nitride light emitting diode according to claim 1, characterized in that: The steps S1 to S7 are all performed in a metal organic chemical vapor deposition device.

5. The method for preparing an aluminum nitride light emitting diode according to claim 1, characterized in that: The thickness of the first AlN layer is 300-320 nm, the thickness of the second AlN layer is 100-250 nm, the thickness of the third AlN layer is 350-650 nm, the thickness of the superlattice transition layer is 500-520 nm, and the thickness of the n-AlGaN layer is 2 μm.

6. The method for preparing an aluminum nitride light emitting diode according to claim 1, characterized in that: The multi-quantum well light-emitting layer includes 5-12 periods, each period includes a well layer located at the lower layer and a barrier layer located at the upper layer, the thickness of the well layer is 2-3nm, and the thickness of the barrier layer is 10nm.

7. The method for preparing an aluminum nitride light emitting diode according to claim 1, characterized in that: The die bonding is to place the light-emitting diode chip on a bracket dotted with a composite filler; the reflow soldering is to melt the solder paste by reflow soldering to fix the light-emitting diode chip; the curing is carried out in a drying oven at a temperature of 120-150° C. for 2-4 hours.

Citation Information

Patent Citations

  • Ultraviolet light emitting diode epitaxial structure and manufacturing method thereof

    CN110364600A

  • Preparation method of large-angle beveled sapphire substrate AlN, light emitting diode and preparation method of light emitting diode

    CN112151645A

  • Aluminum nitride template and preparation method thereof

    CN114284404A

  • Light-emitting diode single crystal growth preparation method

    CN118335858A